2022
DOI: 10.1155/2022/4071081
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application of CT Imaging in Differential Diagnosis and Nursing of Endocrine Tumors

Abstract: In order to investigate the value of preoperative X-ray computed tomography (CT) in predicting the pathological grade of pancreatic neuroendocrine tumors. This paper retrospectively analyzed the CT image examination of pancreatic neuroendocrine tumors, the image characteristics of G-NEC detected by CT image, and the detection of GST by spiral CT. In order to clearly diagnose and evaluate the size and scope of the focus, whether there is adjacent tissue invasion, metastasis, and treatment effect, CT, MR, PET-CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nuclide imaging biomarker is based on a technique that tracks inflammatory activity at molecular level. With tracers containing radioactive elements, nuclide imaging provides evidence for diagnosis and treatment of various conditions (i.e., endocrine tumors ( 70 ), rheumatoid arthritis ( 71 ), etc.). In the field of TED, there has been an expanding utilization of single-photon emission computed tomography (SPECT) and positron emission tomography (PET), with their commonly used tracers including 111Indium-diethylenetriaminepentaaceticacid (DTPA) ( 72 ), 99m-Technetium (99mTc)-DTPA ( 73 – 75 ), Gallium-67 citrate ( 76 ), Gallium-68-DOTA-NOC ( 77 ), etc.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Nuclide imaging biomarker is based on a technique that tracks inflammatory activity at molecular level. With tracers containing radioactive elements, nuclide imaging provides evidence for diagnosis and treatment of various conditions (i.e., endocrine tumors ( 70 ), rheumatoid arthritis ( 71 ), etc.). In the field of TED, there has been an expanding utilization of single-photon emission computed tomography (SPECT) and positron emission tomography (PET), with their commonly used tracers including 111Indium-diethylenetriaminepentaaceticacid (DTPA) ( 72 ), 99m-Technetium (99mTc)-DTPA ( 73 – 75 ), Gallium-67 citrate ( 76 ), Gallium-68-DOTA-NOC ( 77 ), etc.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%